Safety of lifitegrast: A real-world pharmacovigilance study based on FAERS - Chu Zhang; Hui Wang; Xianglei Chen; Yong Liu; Puen Jiang (PLoS ONE, 2025)
To comprehensively assess the safety of Lifitegrast, a drug for dry eye disease, we conducted a comprehensive analysis of adverse event (AE) reports from the FDA Adverse Event Reporting System (FAERS). This retrospective study examined all AE reports submitted between Q3 2016 and Q2 2024, employing disproportionality analysis to identify safety signals associated with Lifitegrast. Out of a total of 13,326,934 AE reports indexed in the FAERS database, 12,393 listed Lifitegrast as the primary suspect drug. A total of 230 ocular AE signals were identified, with 104 of these AEs being detected by different analysis algorithms. Among these signals, 71 AEs were documented in the product insert of Lifitegrast, including but not limited to eye irritation, eye pain and eye swelling. AEs not mentioned in the drug labeling were identified, such as glaucoma and cataracts.AEs associated with Lifitegrast are more commonly observed in male patients and those aged over 65 years.The insights derived from this FAERS database analysis are significant for optimizing the use of Lifitegrast while minimizing potential side effects, thereby enhancing the safety of its clinical application.